O CAD 3D aplicado na validação de protótipos na indústria do vestuário - Pires, Gisely Andressa [UNESP] (2015)
This research discusses the practice of prototyping in the apparel industry. The prototype relates to the construction of a model which is in testing process to be marketed. Currently the most widespread form is the actual construction of the pieces, However there is software on the market that perform this activity virtually. Thus, this study aims to verify the visual similarity between the virtual prototypes and those produced in the traditional process, in order to trim, shape and volume for validation of new projects in the clothing industry. To this end, an exploratory research was conducted, and as a way of addressing the problem were conducted four experiments which include the construction of prototypes for virtual and technical manual.